Analisis Molekuler Regio Core Promoter dan Precore/CoreIsolat Virus Hepatitis B 09IDSKAB-3 - Ibnu Yudistiro; Afiono Agung Prasetyo; Yulia Sari (Nexus Biomedika, 2013)
Background: HBV replicates its DNA genome through reverse transcription from RNA intermediate. It is vulnerable to a high number of mutations during such reverse transcription which are frequently found in core promoter and precore/core regions. This study was aimed to identify genetic variation of HBV core promoter and precore/core regions of 09IDSKAB-3 isolate. Methods: DNA extraction was performed on 09IDSKAB-3 blood sample that was taken from Man Sex with Man Community. Core promoter and precore/core regions were determined by PCR using KL-28 and KL-6 primers and direct sequencing of the corresponding region. Molecular analysis was performed using MEGA 4.0. Results: Based on BLAST result, 09IDSKAB-3 HBV isolate had the highest similarity to isolate AP011085 from DKI Jakarta. Genetic variations A1726C in core promoter, and T1860C, C1877T, G1957C in precore/core region were found in 09IDSKAB-3 isolate. Conclusions: 09IDSKAB-3 HBV isolate was classified into genotype B and subgenotype B3 based on core promoter and precore/core region. The genetic variations found in this isolate may have influence to the replication efficiency and HBeAg/HBcAg production, therefore need further study. Keywords: hepatitis B virus, molecular analysis, core promoter region, precore/core region